Spinal microcircuits go through multiphasic homeostatic compensations in a mouse model of motoneuron degeneration - Filipe Nascimento; M. Görkem Özyurt; Kareen Halablab; Gardave Singh Bhumbra; Guillaume Caron; Marcin Bączyk; Daniel Zytnicki; Marin Manuel; Francesco Roselli; Rob Brownstone; Marco Beato (Cell Reports, 2024)
Summary: In many neurological conditions, early-stage neural circuit adaptation preserves relatively normal behavior. In some diseases, spinal motoneurons progressively degenerate yet movement remains initially preserved. This study investigates whether these neurons and associated microcircuits adapt in a mouse model of progressive motoneuron degeneration. Using a combination of in vitro and in vivo electrophysiology and super-resolution microscopy, we find that, early in the disease, neurotransmission in a key pre-motor circuit, the recurrent inhibition mediated by Renshaw cells, is reduced by half due to impaired quantal size associated with decreased glycine receptor density. This impairment is specific and not a widespread feature of spinal inhibitory circuits. Furthermore, it recovers at later stages of disease. Additionally, an increased probability of release from proprioceptive afferents leads to increased monosynaptic excitation of motoneurons. We reveal that, in this motoneuron degenerative condition, spinal microcircuits undergo specific multiphasic homeostatic compensations that may contribute to preservation of force output.